2021
DOI: 10.1097/opx.0000000000001819
|View full text |Cite
|
Sign up to set email alerts
|

Differential Antimicrobial Efficacy of Multipurpose Solutions against Acanthamoeba Trophozoites

Abstract: SIGNIFICANCE This investigation examines the effectiveness of several common contact lens solutions in the disinfection of Acanthamoeba , which causes a serious eye infection most often resulting from dysfunctional or improper use of contact lens products. PURPOSE Acanthamoeba keratitis is an eye infection caused by a free-living amoeba, which can lead to extensive corneal damage and frequently blindness. Acanthamoeba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…However, while this range of potential contamination activities are ever-present, it’s important that the CLC solutions commonly available to consumers are able to robustly disinfect lenses when used as directed, to otherwise protect patients against the micro-organisms that their lenses may come in contact with. Additionally, it is equally important that products are not only tested in the test tube stand-alone scenario, but also in the real-world common-use scenario involving contact lenses and cases, and that they maintain similar disinfection efficacy to the oft-reported stand-alone results 9 13. It has previously been shown that contact lenses themselves, as well as the contact lens cases packaged with CLCs, can take up biocide out of solution, thereby making any CLC less effective in this real-world situation 7 19…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while this range of potential contamination activities are ever-present, it’s important that the CLC solutions commonly available to consumers are able to robustly disinfect lenses when used as directed, to otherwise protect patients against the micro-organisms that their lenses may come in contact with. Additionally, it is equally important that products are not only tested in the test tube stand-alone scenario, but also in the real-world common-use scenario involving contact lenses and cases, and that they maintain similar disinfection efficacy to the oft-reported stand-alone results 9 13. It has previously been shown that contact lenses themselves, as well as the contact lens cases packaged with CLCs, can take up biocide out of solution, thereby making any CLC less effective in this real-world situation 7 19…”
Section: Discussionmentioning
confidence: 99%
“…Further, while no standard yet exists for determining disinfection efficacy against Acanthamoeba , a protocol for examining this is currently being developed by the American National Standards Institute (ANSI) 14 . Acanthamoeba can also be considered a difficult and differentiating organism to outline the overall disinfection efficacy of any CLC 13 15 16…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced by the increase in the number of investigations into, and publications on Acanthamoeba keratitis in recent years [ 5 , 6 , 8 , 10 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], this is a devastating and potentially sight-threatening disease. However, until now there has been a lack of investigation regarding the behavior of Acanthamoeba on contact lenses, both in and out of contact lens care disinfecting solutions (CLCs).…”
Section: Discussionmentioning
confidence: 99%
“…However, in commercially available MPS, activity is variable even in solutions containing similar formulations of antimicrobial agents [ 6 , 7 , 8 , 9 ]. To overcome this issue, there are newer formulations of MPS, including ACUVUE™ RevitaLens (JnJvision, Jacksonville, FL, USA), which combines the biguanide alexidine with the quaternary ammonium compound polyquaternium-1 (PQ-1), and Biotrue ® (Bausch & Lomb, Rochester, NY, USA), which combines the polyaminopropyl-biguanide (PAPB) with PQ-1 to increase antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%